Homologous recombination repair gene mutations as a predictive biomarker for immunotherapy in patients with advanced melanoma - You, Zhixuan; Lv, Meng; He, Xuanyu; Pan, Yingqin; Ge, Junfeng; Hu, Xue; Zheng, Yating; Huang, Mengli; Zhou, Chengzhi; You, Changxuan (Frontiers in Immunology, 2022)
Background: Nowadays, immunotherapy targeting immune checkpoint receptors is one of the cornerstones of systemic treatment in melanoma. Homologous recombination repair (HRR) is one of the DNA damage response (DDR) pathways, has been proved that correlated to the efficacy of platinum-based chemotherapy, PARP inhibitor therapy and immunotherapy in variety of cancers. However, their predictive value of HRR remained unknown in patients with advanced melanoma. Methods: Data of advanced melanoma patients from an independent cohort (Samstein2018) were used to analyze the correlation with immunogenic markers and the prognostic effect of HRR on immunotherapy, and another four cohorts (Miao2018, Allen 2015, Hugo2016, and Synder2014) are used for validation. Immune infiltration cells scores analyzed by the TCGA-SKCM cohort were used to explore potential mechanisms related to the immune microenvironment. Results: Compared to patients with HRR wild-type (HRRwt), those with HRR mutations (HRRmut) in anti-CTLA-4-treated patients of the Samstein cohort had higher tumor mutation burden (TMB; P=0.0003), objective response rates (ORR; P=0.007), and longer median overall survival (mOS; P=0.014). These findings were further validated in the anti-CTLA-4-treated patients of pooled cohort in terms of the mOS. However, there was no significant correlation between HRRmut and mOS with the anti-PD-1/L1-treated in those cohorts. Subgroup analysis showed that although HRRmut patients showed no significant difference in mOS between anti-CTLA-4 and anti-PD-1 /L1 treatment (P =0.59), the mOS value of anti-CTLA-4 therapy group (24.1 months) inHRRmut patients was numerically superior to the anti-PD-1/L1 therapy group (22.7 months). In contrast, in HRRwt patients, the OS of anti-CTLA-4 therapy group was significantly lower than that of the PD-1/L1 therapy group (10.8 months vs 32.0 months). In addition, transcriptome profiling analysis revealed that 44 (66.7%) genes mutation of HRR pathway associated with reshaping of the immunological microenvironment in melanoma. Conclusions: HRR mutations were associated with a higher TMB level, and better anti-CTLA-4 therapy outcomes. HRR may serve as an independent predictor of anti-CTLA-4 therapy efficacy in patients with advanced melanoma and their clinical value warrants further investigation.